ANALISIS SWOT PENGGUNAAN APLIKASI SPSS DALAM MATA KULIAH STATISTIK PENDIDIKAN PADA MAHASISWA SEMESTER V PRODI PAH UHN I GUSTI BAGUS SUGRIWA DENPASAR - Ni Made Muliani; Ni Made Arini (Padma Sari: Jurnal Ilmu Pendidikan, 2023)
The Education Statistics course is given to students in semester V to introduce students to quantitative data analysis techniques in research in the form of a thesis as a graduation requirement for Strata 1 students. The purpose of this study is to describe the SWOT (strengths, weaknesses, opportunities and threats) analysis of the use of SPSS applications in the Education Statistics course in Semester V students of the Study Program in Hindu Education, Faculty of Dharma Acarya UHN I Gusti Bagus Sugriwa Denpasar. This type of research is descriptive qualitative. This study describes qualitative data obtained from filling out surveys through google forms links. The research findings were that there were 22 variations of answers from students related to strength analysis, there were 12 variations of answers from students related to weakness analysis, there were 7 variations of answers from students related to opportunity analysis and there were 7 variations of answers from students related to threat analysis. The most survey results about strength are answers "more practical in doing data processing" amounting to 15.4%. The largest survey result about weaknesses was the answer "Large application size makes some devices with less high specifications will be heavy enough to run SPSS applications" at 40.4%. The highest survey result was the answer to "Mastering data processing in quantitative research" at 51.9%. The largest survey results on threats are answered: "The data processing process must be based on appropriate steps; Making conclusions from the results of data processing using the SPSS application must be exactly 30.8%.